Academic Quality Compliance Of Public Secondary Schools In The City Schools Division Of San Jose Del Monte Bulacan: Input To Strengthen Institutional Profiling - THELMA MANABAT (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2021)
This study was conducted to determine the level of academic quality compliance of public secondary high schools and its predictors as input to strengthen institutional profiling. The respondents of the study were 167 teachers and school managers in (9) public secondary junior high schools in the City Schools Division of San Jose del Monte Bulacan for the School Year 2017-2018. The descriptive research design was used employing the predictive technique in determining the influence of respondents’ profile, institutions’ profile variables and the management capability factors as the academic quality compliance of the schools. The findings revealed that the schools’ academic quality compliance on leadership and governance is predicted by the NAT (Beta = .431), promotion rate (Beta= 1.170), and enrollment rate (Beta = .747). The management capability on quality instruction predicts the schools’ academic quality compliance on curriculum and learning (Beta = .971) and the academic quality compliance on accountability and continuous improvement is influenced by the management capability on quality instruction. The promotion rate of the school predicts the academic quality compliance of the school in the area of management of resources (Beta =.671). The hypothesis stating that the respondent's profile, institutional profile, and management capability, singly or combination predict the schools' academic quality compliance is partly sustained. .